VALIDATION OF MAXIMUM OXYGEN CONSUMPTION (VO2 MAX) WITH SOCIETY OF THORACIC SURGEON (STS) RISK SCORE IN PREOPERATIVE ASSESSMENT OF PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFT (CABG) SURGERY: A PILOT STUDY - Chaudhry, Imtiaz Ahmad; Pervaiz, Farrah; Ahmed, Kaleem; Naseer, Mehwish; Siddiqa, Aysha; Khalil, Hafsa; Iqbal, Muhammad Afsheen (Pakistan Armed Forces Medical Journal, 2021)
Objective: To validate VO2 max testing with society of thoracic surgeon (STS) score in the preoperative assessment of patients undergoing coronary artery bypass graft surgery. Study Design: This was a single center and observational study. Place and Duration of Study: Armed Forces Institute of Cardiology and National Institute of Heart Diseases, Rawalpindi Methodology: Forty four adult patients undergoing elective on pump coronary artery bypass graft surgery with an EF of >45% were included in this study as per inclusion criteria through non probability consecutive sampling. Five patients were lost to follow up. In 39 patients preoperative society of thoracic surgeons scoring was done and VO2 max of these patients was calculated. After coronary artery bypass graft surgery these patients were followed for mortality and morbidity. The discriminative capacity of VO2 max was compared with the STS risk scoring system using Receiver Operating Characteristic curves (ROC-curves). Results: We analyzed the data of 39 patients male 35 (89.7%), female 4 (10.3%). Mean age of our study population was 55.0 ± 10.2 years and a mean BMI of 26.8 ± 3.81. There were 20 (54.1%) hypertensives, 2 (5.4%) diabetics and 5 (13.5%) smokers. There was only one patient with a history of previous myocardial infarction. Majority of the patients belonged to NYHA class II 30 (76.9%) with a mean EF of 56.6 ± 5.17. Prolonged Ventilation (>24 hrs) was significantly associated with lesser values of VO2 max with a p-value of 0.01. Similarly, post-operative mortality and prolonged hospital stay in the low VO2 max groups correlated with the trends predicted by the society of thoracic surgeons scoring system. Conclusion: We conclude from this study that low preoperative VO2 max levels correlated well with STS scoring system for predicting mortality, ventilation time and length of hospital stay.